Pengaruh Senam Hamil Terhadap Kualitas Tidur pada Ibu Hamil di Wilayah Kerja BLUD UPTD Puskesmas Bumi Rahayu Kecamatan Tanjung Selor Kabupaten Bulungan - Umi Wakhidah; Gajali Rahman; Rahmawati Wahyuni (Media of Health Research, 2023)
Sleep disorders in the second and third trimesters of pregnancy are due to discomfort such as low back pain due to compensation from the enlargement of the uterus to an anterior position, lordosis which shifts the center of gravity backward towards the two legs causing fatigue. The physiological conditions of pregnancy and psychological changes can trigger sleep disturbances in pregnant women. Pregnancy exercise is an option of non-pharmacological therapy so that it can improve the quality of mother's sleep during pregnancy. To determine the effect of pregnancy exercise on sleep quality of pregnant women in the working area of the BLUD UPTD Puskesmas Bumi Rahayu. The type of research used in this research is experimental research. The research design was one group pretest-posttest without control. The population of this study were all pregnant women in the second and third trimesters who were recorded as pregnant from August 2022, as many as 19 people in the BLUD UPTD work area of the Bumi Rahayu Health Center in 2022. The sample used in this study was total sampling, namely 19 respondents. Data analysis was carried out, namely bivariate analysis using the Wilcoxon test. Statistical test analysis showed that the sleep Quality in pregnant women variable was obtained (p-value 0.000<α<0.05). These results explain that there is a significant effect of pregnancy exercise on sleep quality (p-value < α = 0.05).